HIV LTR-Driven Antisense RNA by Itself Has Regulatory Function and May Curtail Virus Reactivation From Latency - Kobayashi-Ishihara, Mie; Terahara, Kazutaka; Martinez, Javier P.; Yamagishi, Makoto; Iwabuchi, Ryutaro; Brander, Christian; Ato, Manabu; Watanabe, Toshiki; Meyerhans, Andreas; Tsunetsugu-Yokota, Yasuko (Frontiers in Microbiology, 2018)
Latently infected T lymphocytes are an important barrier towards eliminating a persistent HIV infection. Here we describe an HIV-based recombinant fluorescent-lentivirus referred to as “rfl-HIV” that enables to analyze sense and antisense transcription by means of fluorescence reporter genes. This model virus exhibited similar transcriptional and functional properties of the antisense transcript as observed with a wild type HIV, and largely facilitated the generation of latently-infected T cells clones. We show that latently-infected cells can be divided into two types, those with and those without antisense transcription. Upon addition of latency reversal agents, only the cells that lack antisense transcripts are readily reactivated to transcribe HIV. Thus, antisense transcripts may exhibit a dominant suppressor activity and can lock an integrated provirus into a non-reactivatable state. These findings could have important implications for the development of strategies to eradicate HIV from infected individuals.